Normal mode analysis of Zika virus. (February 2018) - Lee, Byung Ho; Jo, Soojin; Choi, Moon-ki; Kim, Min Hyeok; Choi, Jae Boong; Kim, Moon Ki
Graphical abstract: Highlights: Dynamic properties of ZIKV are investigated using normal mode analysis based on symmetry constrained elastic network model. The change of vibrational potentials gives insights into the ZIKV assembly mechanism from asymmetric unit structures to a shell structure. This vibration study implies that the flexibility of glycosylation sites plays a crucial role in the biological functions of ZIKV. Abstract: In recent years, Zika virus (ZIKV) caused a new pandemic due to its rapid spread and close relationship with microcephaly. As a result, ZIKV has become an obvious global health concern. Information about the fundamental viral features or the biological process of infection remains limited, despite considerable efforts. Meanwhile, the icosahedral shell structure of the mature ZIKV was recently revealed by cryo-electron microscopy. This structural information enabled us to simulate ZIKV. In this study, we analyzed the dynamic properties of ZIKV through simulation from the mechanical viewpoint. We performed normal mode analysis (NMA) for a dimeric structure of ZIKV consisting of the envelope proteins and the membrane proteins as a unit structure. By analyzing low-frequency normal modes, we captured intrinsic vibrational motions and defined basic vibrational properties of the unit structure. Moreover, we also simulated the entire shell structure of ZIKV at the reduced computational cost, similar to the case of the unit structure, by utilizing its icosahedral symmetry. From the NMA results, we can not only comprehend the putative dynamic fluctuations of ZIKV but also verify previous inference such that highly mobile glycosylation sites would play an important role in ZIKV. Consequently, this theoretical study is expected to give us an insight on the underlying biological functions and infection mechanism of ZIKV.